Insights into current limitations of density functional theory - Cohen, Aron J; Mori-Sánchez, Paula; Yang, Weitao (Science (American Association for the Advancement of Science), 2008)
Density functional theory of electronic structure is widely and successfully applied in simulations throughout engineering and sciences. However, for many predicted properties, there are spectacular failures that can be traced to the delocalization error and static correlation error of commonly used approximations. These errors can be characterized and understood through the perspective of fractional charges and fractional spins introduced recently. Reducing these errors will open new frontiers for applications of density functional theory.